Quantification and mapping of fish waste in retail trade and restaurant sector: Experience in Emilia-Romagna, Italy. (November 2021) - Greggio, Nicolas; Serafini, Alba; Balugani, Enrico; Carlini, Carlotta; Contin, Andrea; Marazza, Diego
Graphical abstract: Highlights: Fish waste quantification at distribution and consumption level in a 4 M inh. region. Large supermarkets and large restaurants produce 0.2 and 0.1 Mg/week per store. Fishmongers are the less relevant source at the distribution level (0.06 Mg/week) Fish waste is 0.5–3 kg/y per capita, corresponding to 1–10% of annual consumption. Household fish waste production amount 2300 up to 4000 Mg/y close to restaurants. Abstract: The circular economy approach imposes the complete recovery of components, materials and energy from waste. Many active compounds with biomedical and nutraceutical applications can be extracted by Fish Waste (FW), but few are the operating industrial plants. Quantification and mapping of the potential FW availability along the entire fish value-chain is crucial in fostering its actual valorisation. Apart at industrial processing, in the distribution segment the estimation of FW availability is absent. This paper aimed to quantify and locate FW generated by point sources such as supermarkets, fishmongers and restaurants as well as to establish the diffuse domestic FW production in a 4, 5M inhabitants region. The study provides an exportable method and indications for comparable worldwide areas. A simplified valorisation scenario for equivalent biomethane production is also presented. Direct interviews and indirect approach based on fish consumption have been adopted and compared. Large supermarkets and medium-large restaurants are the main FW producers (239 and 125 kg/week, respectively) followed medium-large fishmongers and medium supermarkets (63 and 86 kg/week, respectively). In the investigated region the larger FW point sources are supermarkets (average 3000 Mg/y), while fishmongers are the smaller (average 750 Mg/y). Restaurants (average 1400 Mg/y) show the wider range of variability between 460 and 8000 Mg/y. The indirect methodology reveals that domestic FW production ranges from 2376 to 3961 Mg/y. Per capita estimations of FW ranged from 0.5 − 3 kg/y. The economic value of FW (biomethanation route) is 68 EUR/Mg. A qualification as "highly potential waste" would promote FW valorization.